Privacy Management of Sexting in Young Adult's Dating Relationships - Kirana, Dewi Chandra; Hendriyani, Hendriyani (JURNAL KOMUNIKASI INDONESIA, 2023)
Abstract: This study explains young people's experience in Indonesia with their privacy management regarding sexting in dating relationships. The research uses Communication Privacy Management (CPM) Theory. This study uses qualitative research, collecting data by doing in-depth interviews with 10 informants of young adults who have sexting with their partners. Thematic analysis of the data finds that how informants perceive sexting, the function of sexting in their relationship, and the risk of sexting influence the way they carry out privacy management. The informants think it strengthens the connection and trust with their partners. However, they are fully aware of the risk of sexting: the text could easily leak to others, which could be harmful to their reputation. There are influences from gender and cultural context on what is called privacy and its risks. Therefore, they implement very complex privacy management, such as choosing the safest chat application; making rules about how the pictures or videos must not show a background that can be used to identify the sender of sexting; and keeping the passwords of all social media accounts owned by their partners. They also have their own 'language,' by using emoticons and codes, which are only understood by them and their partners. Hence, those who engage in sexting protect their privacy by establishing complex privacy boundaries that they mutually agree on.